The Role of Orai1 in Regulating Sarcoplasmic Calcium Release, Mitochondrial Morphology and Function in Myostatin Deficient Skeletal Muscle - Sztretye, Mónika; Singlár, Zoltán; Balogh, Norbert; Kis, Gréta; Szentesi, Péter; Angyal, Ágnes; Balatoni, Ildikó; Csernoch, László; Dienes, Beatrix (Frontiers in Physiology, 2020)
In mice a naturally occurring 12-bp deletion in the myostatin gene is considered responsible for the compact phenotype (MstnCmpt-dl1Abc, Cmpt) labeled by a tremendous increase in body weight along with signs of muscle weakness, easier fatigability, decreased Orai1 expression and store operated calcium entry (SOCE). Here, on the one hand, Cmpt fibers were reconstructed with venus-Orai1 but this failed to restore SOCE. On the other hand, the endogenous Orai1 was silenced in fibers from wild type C57Bl6 mice which resulted in 70% of Orai1 being silenced in whole muscle homogenates as confirmed by Western blot, accompanied by an inhibitory effect on the voltage dependence of SR calcium release that manifested in a slight shift towards more positive potential values. This maneuver completely hampered SOCE. Our observations are consistent with the idea that Orai1 channels are present in distinct pools responsible for either a rapid refilling of the SR terminal cisternae connected to each voltage-activated calcium transient, or a slow SOCE associated with an overall depletion of calcium in the SR lumen. Furthermore, when Cmpt cells were loaded with the mitochondrial membrane potential sensitive dye TMRE, fiber segments with depolarized mitochondria were identified covering on average 26.5±1.5% of the fiber area. These defective areas were located around the neuromuscular junction and displayed significantly smaller calcium transients. The ultrastructural analysis of the Cmpt fibers revealed changes in the mitochondrial morphology. In addition, the mitochondrial calcium uptake during repetitive stimulation was higher in the Cmpt fibers. Our results favor the idea that reduced function and/or expression of SOCE partners (in this study Orai1) and mitochondrial defects could play an important role in muscle weakness and degeneration associated with certain pathologies, perhaps including loss of function of the neuromuscular junction and aging.